Staffing organizations - Judge, Timothy A.; Kammeyer-Mueller, John (McGraw-Hill, 2022)
"This edition has been the beneficiary of major restructuring and updating to ensure continuing alignment of the material with current in-the-field business practices. The changes range from small inclusions of new stand-ards to major chapter revisions. The new structure will make it easier for students to see how each part of the staffing process proceeds from begin-ning to end, and it will also help them see how the topics fit together to create a cohesive staffing management system. The human resources landscape continues to be transformed by technolo-gy, and this edition of the textbook reflects this influence. The use of human resources information systems for tasks like recruitment, selection, and forecasting is now thoroughly integrated into all sections. The role of social media, the Internet, and other information management tools is emphasized in several chapters, and new examples from companies keep the application of concepts fresh and current"--